Hubungan Pola Komunikasi Orang Tua dengan Perilaku Kesehatan Reproduksi Remaja di SMK Negeri 15 Kota Bekasi - Siti Khoiriyah; Dinayah Hasan (Pusat Riset dan Inovasi Nasional, 2023)
Adolescence is a period marked by significant physical and psychosocial changes. These changes have potential risks that can affect an individual's future. One of the factors that increase the risk is the lack of knowledge and communication by parents to their children regarding reproductive health behavior. This study aims to determine the relationship between parental communication patterns and adolescent reproductive health behavior at SMK Negeri 15 Kota Bekasi. The type of quantitative research with a cross-sectional approach. The sample used was 34 respondents. The analysis used was univariate and bivariate. The results of the study showed that the communication patterns of parents with adolescents were mostly in the good category (91.2%). Adolescent reproductive health behavior was mostly in the less good category (70.6%). The results of the chi-square statistical test obtained a p value = 0.539, meaning there was no relationship between parental communication patterns and adolescent reproductive health behavior. There was no significant relationship between parental communication patterns and adolescent reproductive health behavior. Although effective communication between parents and adolescents is important, it is not enough to guarantee good reproductive health behavior among adolescents.